Implementasi Algoritma Kriptografi RSA untuk Enkripsi dan Dekripsi Email - Albert Ginting; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
In the world of Internet nothing is really safe. There's always a gap in any application made. Likewise in email delivery. To minimize attacks on the data transmission is usually applied cryptography. One fairly popular cryptographic algorithms are RSA algorithm. In this study will discuss the implementation of a cryptographic algorithm RSA encryption and decryption process email. To test created a java-based email client program with message encryption and decryption features messages. This application uses the Java programming language and Netbeans 7.4 as editor. Mail servers used is Google Mail. The initial step of this study was to download email from the Google server and encrypt the message. The second step is decrypt the message to verify whether the message is still the same as the original message before it is encrypted . Results from this study is the application that can encrypt and decrypt messages using RSA cryptographic algorithm. With this application is expected to mail delivery is much safer. Because encrypted email will generate a random decimal number of unknown value .